Accompanying training professionalization processes, using didactic and research in a complex perspective - Frisch, Muriel (Form@re - Open Journal per la formazione in rete, 2018)
The lack of reference to didactics obscures the perspective on the relationship to knowledge. It seems to us, however, that professionalization through training and a complex skills-based approach both imply integrating knowledge, knowledge constructions and devices; connecting elements together and reflecting on conceptualization processes in order to learn more dynamically without neglecting didactic innovations. How could new forms of complexity be re-established in pedagogy while bridging training-research with didactic research? Which frameworks and teaching tools would be needed to enable progress? In this article, after contextualizing our theoretical work and frameworks, we will present the emergence of a complex model connecting information-savoir and connaissance with pratiques-expérience-expérimentation-exploration-expertise-compétence-(re)-connaissance; a feedback on the concept of contre-transposition and the problematization approach for the purpose of (re)constructing professional skills. We will then use a flipped classroom method to try to understand how a teacher-in-training builds construction indices of his or her professionalism in interaction with pupils and teachers’ actions. Accompagnare i processi di professionalizzazione attraverso una prospettiva complessa di formazione e ricerca I mancati riferimenti alla didattica impediscono di mettere in luce la prospettiva legata al rapporto con la conoscenza. Ci sembra, tuttavia, che la professionalizzazione attraverso la formazione e un approccio complesso basato sulle competenze implichi l’integrazione di conoscenze, costruzioni di conoscenze e dispositivi da un lato, ed il collegamento, dall’altro, di elementi di riflessione sui processi di concettualizzazione che supportino un apprendimento dinamico senza trascurare le innovazioni didattiche. Come possono essere ristabilite nuove forme di complessità in pedagogia attraverso l’interazione tra ricerca-formazione e ricerca legata alla didattica? Quali framework e strumenti didattici sono necessari per promuovere il progresso? Nel presente articolo, dopo aver contestualizzato il quadro teorico di riferimento, illustriamo un modello complesso che collega informazioni-conoscenza e comprensione con pratiche-esperienza-sperimentazione-esplorazione-expertise-competenza-(re)-conoscenza. Forniamo inoltre alcune riflessioni sul concetto di contrasposizione e sull’approccio che problematizza la (ri)costruzione delle competenze professionali. Utilizzeremo quindi un metodo di flipped classroom per comprendere come un docente in formazione possa costruire indici per la definizione della sua professionalità nell’interazione con gli allievi e con le azioni degli altri docenti.